2021
DOI: 10.1007/s10552-021-01493-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends, tumor characteristics and stage-specific survival in penile non-squamous cell carcinoma vs. squamous cell carcinoma

Abstract: Purpose To compare Cancer-specific mortality (CSM) in patients with Squamous cell carcinoma (SCC) vs. non-SCC penile cancer, since survival outcomes may differ between histological subtypes. Methods Within the Surveillance, Epidemiology and End Results database (2004–2016), penile cancer patients of all stages were identified. Temporal trend analyses, cumulative incidence and Kaplan–Meier plots, multivariable Cox regression and Fine and Gray competing-risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Wenzel, et al, stated that this type of SCC was found more frequently. 24 A study by Zamzami, et al, in Arifin Achmad Regional General Hospital, Pekanbaru, Indonesia, also found that 100% of cases are squamous cell carcinoma. 7 While this study found 86.2% were SCC types.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wenzel, et al, stated that this type of SCC was found more frequently. 24 A study by Zamzami, et al, in Arifin Achmad Regional General Hospital, Pekanbaru, Indonesia, also found that 100% of cases are squamous cell carcinoma. 7 While this study found 86.2% were SCC types.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that certain non-SCC types may have a less promising outcome than SCC types; penile melanoma and genitourinary sarcoma are neoplasms with a poor prognosis and have a high rate of recurrence even after surgery. 24 Carcinoma of the penis at an early stage is generally easier to treat. 4 Local therapy approaches can include penile-sparing techniques and topical chemotherapy using 5-fluorouracil and imiquimod.…”
Section: Discussionmentioning
confidence: 99%
“…As in all SEER-based analyses, comorbidities were not available and could lead to confounding of CSM rates. Finally, due to small sample sizes, we grouped patients within unconventional urethral-cancer histologies, as previously reported for unconventional histologies [ 30 ]. As a result, it is possible that some of these individual subtypes of unconventional histologies may have more favorable survival than others or vice versa (e.g., in lymphomas).…”
Section: Discussionmentioning
confidence: 99%
“…[16] Meanwhile, other studies reported differences in mortality risk between penile cancer subtypes of SCC and non-SCC, where non-SCC subtypes were associated with an increased of mortality. [21] Despite this controversy, existing studies have shown the usual SCC subtype to have a lower mortality risk than the other subtypes.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…[9] Similar proportions were found in two studies that found the cancer subtype to predict mortality. [16,21] Rare cases of penile cancer other than the usual subtype of SCC cause the resulting estimate to be less accurate. More studies with larger sample sizes are needed to reach an academic consensus on the role of subtypes in the mortality prognosis of penile cancer.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%